Drivers of diatom production and the legacy of eutrophication in two river plume regions of the northern Gulf of Mexico - Krause, Jeffrey W.; Boyette, Adam D.; Marquez, Israel A.; Pickering, Rebecca A.; Maiti, Kanchan (Frontiers in Marine Science, 2023)
In the northern Gulf of Mexico (nGoM), the Louisiana Shelf (LS) and Mississippi Bight (MB) subregions are influenced by eutrophication to varying degrees. Despite recognition that dissolved silicon may regulate diatom productivity in the nGoM, there is only one published data set reporting biogenic silica (bSiO2) production rates for each subregion. We report that bSiO2 production rates on the LS and MB are high and appear to be controlled by different nutrients among seasons. Despite exceptional upper trophic level biomass regionally, which suggests significant primary production by diatoms (as in other systems), gross euphotic-zone integrated bSiO2 production rates are lower than major bSiO2 producing regions (e.g. upwelling systems). However, when normalizing to the depth of the euphotic zone, the bSiO2 production rates on the LS are like normalized rates in upwelling systems. We suggest local river-plume influenced hydrography concentrates diatom productivity within shallow euphotic zones, making production more accessible to higher trophic organisms. Comparison of rates between the LS and MB suggest that the fluvial nitrate within the LS stimulates bSiO2 production above that in the MB, which has a smaller watershed and is less eutrophic (relatively). Beyond understanding the factors controlling regional bSiO2 production, these data offer the most comprehensive Si-cycle baseline to date as the LS and MB will likely exchange freely in the mid to late century due to land subsidence of the Mississippi River delta and/or sea-level rise.